A systematic review on the relationship between antisocial, borderline and narcissistic personality disorder diagnostic traits and risk of violence to others in a clinical and forensic sample. Issue 1 (December 2016) - Lowenstein, Joe; Purvis, Charlotte; Rose, Katie
Abstract Risk assessments identify the presence of a Personality Disorder diagnosis as relevant to future violence. At present, risk assessments focus on the presence of the disorder rather than identifying key traits related to risk. Systematic searches of three databases were conducted from January 2000 until August 2014. Of 92, 143, 15 studies met the inclusion criteria. A lack of empirical research was found focusing on individual traits; instead most considered PD diagnosis as a sole entity. A preliminary model has been developed detailing the link between potential interactions of diagnostic traits and risk of violence. Recommendations for future research are made.